Time trends in mortality of congenital heart disease in children aged 0–14 years: a global, regional, and national cohort analysis from 1990 to 2021 using the global burden of disease study - Xu, Jiaoli; Li, Qinhong; Xiong, Jingxuan; Cheng, Zugen; Deng, Lili (Frontiers in Public Health, 2025)
IntroductionCongenital heart disease (CHD) represents a significant global public health burden, with substantial variability in mortality rates across different regions and age groups.MethodsThis study utilized the Global Burden of Disease (GBD) database to examine trends in CHD-related mortality among children aged 0-14 from 1990 to 2021.ResultsWe report a 55.34% reduction in CHD-related deaths among children, with global mortality rates decreasing from 28.63 per 100,000 in 1990 to 11.06 per 100,000 in 2021. Notably, the decline in mortality was more pronounced in younger children, with the highest burden observed in the Low socio-demographic index (SDI) region, where CHD-related mortality rates remain disproportionately high. In contrast, the high SDI region experienced the greatest improvements in mortality reduction. Regional disparities are also evident, with South Asia bearing the highest number of CHD-related deaths, while Oceania exhibited the highest mortality rate.DiscussionThese trends underscore the need for continued global efforts to reduce CHD-related mortality, particularly in low-income regions, and to address the disparities in healthcare access and outcomes. Our findings highlight the ongoing challenges in pediatric cardiology and the need for targeted interventions to sustain improvements in CHD survival, especially for neonates and infants.